Driving Innovation to Support Pupils with SEND Through Co-Production in Education and Research: Participatory Action Research with 22q11.2 Deletion Syndrome Families in England - Michelle Jayman; Sophie Edmonds; Maria Gudbrandsen (Behavioral Sciences)
Children and young people (CYP) with special educational needs and disabilities (SEND) comprise over 1.6 million pupils in classrooms in England. However, evidence suggests pupils’ learning and wellbeing needs are often missed or unmet and legislation designed to increase families’ decision-making in education provision has not been translated into practice. The current participatory action research study investigated the perceptions and experiences of a specific population of SEND pupils in mainstream schooling—CYP with 22q11.2 deletion syndrome (22q). Participants included existing and previous mainstream pupils and their parents (n = 8 parent−CYP dyads). Data were collected through semi-structured interviews, and a hybrid inductive-deductive thematic analysis was conducted. Five superordinate themes were generated: minding the gaps in school support; my mental wellbeing story; power and influence; getting it wrong: failing CYP and families; and getting it right: from surviving to thriving. Findings provided authentic insights into the lived experiences of support for CYP with 22q which resonate with the wider SEND population. These findings can help to inform more inclusive practice in mainstream settings. An affirmative model which places SEND pupils and parents at the heart of meaningful reform is urgently needed in schools. Collaborative work among all key stakeholders is paramount to ensure that strategies are genuinely co-produced, co-owned and robustly evidence-based.